2016
DOI: 10.1017/s175173111500292x
|View full text |Cite
|
Sign up to set email alerts
|

The variation in the eating quality of beef from different sexes and breed classes cannot be completely explained by carcass measurements

Abstract: Delivering beef of consistent quality to the consumer is vital for consumer satisfaction and will help to ensure demand and therefore profitability within the beef industry. In Australia, this is being tackled with Meat Standards Australia (MSA), which uses carcass traits and processing factors to deliver an individual eating quality guarantee to the consumer for 135 different 'cut by cooking methods' from each carcass. The carcass traits used in the MSA model, such as ossification score, carcass weight and ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 28 publications
1
17
0
2
Order By: Relevance
“…It has already been shown that such a system would be well accepted (Hocquette et al, 2011) and could be based upon the Meat Standards Australia (MSA) model (Watson et al, 2008a) which uses predictors such as carcase weight, ossification, rib fat and intramuscular fat to predict consumer eating quality. Indeed, Bonny et al (2016a and2016b) have previously shown that this model functions well when using European beef, with only minor adjustments. However, it is unclear if a single quality descriptor would be applicable to all European consumers.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has already been shown that such a system would be well accepted (Hocquette et al, 2011) and could be based upon the Meat Standards Australia (MSA) model (Watson et al, 2008a) which uses predictors such as carcase weight, ossification, rib fat and intramuscular fat to predict consumer eating quality. Indeed, Bonny et al (2016a and2016b) have previously shown that this model functions well when using European beef, with only minor adjustments. However, it is unclear if a single quality descriptor would be applicable to all European consumers.…”
Section: Introductionmentioning
confidence: 87%
“…The carcasses used for this experiment were described in detail by Bonny et al (2016a) and Legrand et al (2013). Briefly, the data set was formed through combining the records of a number of specific, smaller, experiments.…”
Section: Animals and Muscle Samplesmentioning
confidence: 99%
“…The carcasses used for this experiment are described in detail by Bonny et al (2016a). Briefly, the data set was formed through combining the records of a number of specific, smaller, experiments.…”
Section: Animals and Muscle Samplesmentioning
confidence: 99%
“…Much of the literature indicates that tenderness is the most important factor in determining consumer satisfaction (Verbeke et al 2010) even if, according to Bonny et al (2016Bonny et al ( , 2017, tenderness, flavour and overall liking appear to have similar weights. The fact that French people are generally satisfied with the quality of beef confirms the results of Normand et al (2014).…”
Section: Trends and Drivers Of Beef Consumption And Perceptionmentioning
confidence: 99%
“…Nevertheless, the beef industry must make progress in terms of offering meat that is more tender, and tastes better but also with a reduced variability in eating quality: it would be preferable that purchasing identical cuts of meat could give similar eating quality outcomes. Indeed, today, there is no clear link between the price of beef for the consumer and the taste quality of this meat in France (Normand et al 2014) as producers are paid based on the carcase characteristics (conformation and fattening), which have little relationship to the taste quality of the meat (Bonny et al 2016).…”
Section: Trends and Drivers Of Beef Consumption And Perceptionmentioning
confidence: 99%